Peningkatan Kesadaran Lingkungan Melalui Penerapan Model Contoh Terpadu: Studi Eksperimen Pada Masyarakat Rawan Lingkungan di Sulawesi Selatan - H. Djaali (Universitas Negeri Malang, 2016)
Enhancing environmental awareness through an integrated model is more effective than common councelling and without any councelling for people living at the slum area in South Sulawesi. This hypothesis was tested by an experimental study using 6 groups, three of which were nomadic farmers and the other three coastal people. Three variables were being measured, namely knowledge and comprehension concerning environmental problems, attitude towards the environment, and environmental behavior.